Longitudinal relaxation of mechanically free KH₂PO₄ type crystals. Piezoelectric resonance and sound attenuation - Levitskii, R.R.; Zachek, I.R.; Moina, A.P.; Vdovych, A.S. (Condensed Matter Physics, 2008)
Within the framework of proton model with taking into account the piezoelectric interaction with the shear strain ε₆, a dynamic dielectric response of KD₂PO₄ type ferroelectrics is considered. Experimentally observed phenomena of crystal clamping by high frequency electric eld, piezoelectric resonance and microwave dispersion are described. Ultrasound velocity and attenuation are calculated, peculiarities of their temperature dependence at the Curie points are described. Existence of a cut-off frequency in the frequency dependence of attenuation is predicted. В рамках протонної моделi з врахуванням п’єзоелектричної взаємодiї зi зсувною деформацiєю ε₆ розглянуто динамiчний дiелектричний вiдгук сегнетоелектрикiв типу KD₂PO₄. Враховано динамiку п’єзоелектричної деформацiї. Явно описано явища затискання кристалу високочастотним електричним полем, п’єзоелектричного резонансу i НВЧ дисперсiї, що спостерiгаються на експериментi. Розраховано коефiцiєнт поглинання звуку. Описано особливостi коефiцiєнта поглинання в околi точок переходу. Передбачено наявнiсть обрiзаючої частоти у частотнiй залежностi коефiцiєнта поглинання звуку.